2006
DOI: 10.1111/j.1600-0714.2006.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for oral hairy leukoplakia in HIV‐infected adults of Brazil

Abstract: Prevalence of OHL was 28.8%. Viral load, oral candidiasis, previous use of fluconazole, and systemic acyclovir were determined to be risk factors for OHL. Antiretroviral medication proved to be protective against the development of OHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(102 reference statements)
2
14
1
7
Order By: Relevance
“…This was in contrast to other studies where OHL was associated to high HIV viral load [9, 24, 30]. Patton et al found that patients with OHL were twofold more likely to have a higher viral load than people without oral lesions [30], whereas Moura et al had suggested OHL as a clinical marker for HIV viral load >3000 copies/ μ L [31]. Our finding of negative correlation for OHL should be explored in future studies whether there is any difference in relationship between OHL and high viral loads in developing and developed nations.…”
Section: Discussionmentioning
confidence: 75%
“…This was in contrast to other studies where OHL was associated to high HIV viral load [9, 24, 30]. Patton et al found that patients with OHL were twofold more likely to have a higher viral load than people without oral lesions [30], whereas Moura et al had suggested OHL as a clinical marker for HIV viral load >3000 copies/ μ L [31]. Our finding of negative correlation for OHL should be explored in future studies whether there is any difference in relationship between OHL and high viral loads in developing and developed nations.…”
Section: Discussionmentioning
confidence: 75%
“…Likewise, the HL cases occurred at viral loads far below the ones related with the risk of opportunistic HL. 10 The only event not occurring above 200 CD4þ T-cells/mL was the oral KS case, but showed a rapid deterioration pattern that is consistent with IRIS, 11 and certainly not expected as opportunistic in people with such a good response to treatment and a good CD4þ T-cell recovery. We thus consider the finding of this KS IRIS as a control validating the capacity of our methodology.…”
Section: Discussionmentioning
confidence: 80%
“…However, risk indicators described in the literature are variable according to studied population. Risk indicators for OHL in Brazilian HIVinfected adults were viral load, OC, and use of fl uconazole or acyclovir, while antiretroviral drugs were shown to be protective for OHL (Moura et al, 2006 ). CD4 count and antiretroviral drug were relevant risk indicators for OC and OHL in HIV-infected adults of North Carolina, but smoking was an important risk indicator just for OC (Chattopadhyay et al, 2005b ).…”
Section: Ohl Classifi Cation Etiology and Risk Indicatorsmentioning
confidence: 98%
“…They have been accepted as markers of immunosuppression (Miziara and Weber 2006 ;Reginald and Sivapathasundharam 2010 ;Patton et al, 2013 ), contributing for the early identifi cation of HIV infection or AIDS (Dias et al, 2012 ). In addition, OHL and OC can be a sign to warn dentists on the decreasing immunological condition of HIVinfected patients (Moura et al, 2006 ;Sontakke et al, 2011 ;Bodhade et al, 2011 ). Although OC appears to be a superior indicator of immune decline and virologic levels in individuals submit to highly active antiretroviral therapy (HAART), the presence of OHL and OC simultaneously has also been observed as an indicator of low CD4 count and high viral load (Miziara and Weber 2006 ).…”
Section: Oral Candidiasis Oral Hairy Leukoplakia and Hiv Infectionmentioning
confidence: 99%